PENGEMBANGAN E-MODUL KERAGAMAN BUDAYA INDONESIA BERBASIS TPACK TERINTEGRASI TRI N UNTUK MENINGKATKAN DIMENSI KREATIF SISWA - Novita Sakti Dewanti; Heri Maria Zulfiati; Sutrisna Wibawa (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This development research was carried out based on the results of observations and interviews conducted at one of the elementary schools in Sleman Regency. It is known that class IV students do not yet understand the various kinds of cultural diversity that exist in Indonesia because Indonesia has a lot of cultural diversity. This happens because the teaching materials used by teachers are still limited. Teachers only focus on printed teaching materials, so learning seems a little monotonous or limited to books. This research aims to produce practical teaching materials for Indonesian cultural diversity e-modules based on Tri N Integrated TPACK to increase students' creative dimensions. The development model used is ADDIE, which consists of five stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Through the media, material, and language validation stage, a result of 82.17% was obtained so that the new module was suitable for use. while the student response was 86.5%. Acceptability at a practical level can be used by students in social studies learning and Pancasila education, which includes material about Indonesia's cultural diversity.